2018
DOI: 10.36226/jrmb.v3i3.158
|View full text |Cite
|
Sign up to set email alerts
|

Stres Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan

Abstract: This study aims to determine the effect of work stress and work discipline on employee performance at Manggarai Station, South Jakarta. The type of research used is probability sampling with a quantitative approach. The sample used in this study used a simple random sampling technique. The data obtained are primary data from the results of respondents' answers to questionnaires distributed by 115 respondents and processed using the SPPS (Statistic Product and Service Solution) software program 17. In the f tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 2 publications
0
6
0
12
Order By: Relevance
“…Employee performance is the result produced by certain work functions or activities on a particular job over a certain period of time, showing the quality and quantity of the work (Bernardin and Russell, 2015:270). Some previous research related to this research such as research conducted by Setiawati (2017), Setyawati et al (2018) and Limbong et al (2019), the results of their research showed that work discipline and work stress affect employee performance.…”
Section: Introductionmentioning
confidence: 76%
“…Employee performance is the result produced by certain work functions or activities on a particular job over a certain period of time, showing the quality and quantity of the work (Bernardin and Russell, 2015:270). Some previous research related to this research such as research conducted by Setiawati (2017), Setyawati et al (2018) and Limbong et al (2019), the results of their research showed that work discipline and work stress affect employee performance.…”
Section: Introductionmentioning
confidence: 76%
“…Menurut Izzah & Ardiani (2016) menyebutkan bahwa disiplin kerja merupakan sikap dan perilaku karyawan supaya patuh kepada peraturan yang berlaku. Menurut Setyawati et al (2018) menyebutkan bahwa perusahaan akan sulit mewujutkan tujuannya tanpa dukungan disiplin kerja karyawan. Menurut Menurut Dunggio (2013) menyebutkan bahwa organisasi sulit untuk mencapai hasil yang optimal, jika tidak didukung dengan disiplin yang bauk.…”
Section: Kajian Pustakaunclassified
“…Menurut Adha, Qomariah and Hafidzi (2019) kinerja karyawan adalah suatu hasil yang dicapai oleh karyawan, dimana hasil kerja tersebut dapat diperlihatkan buktinya secara konkrit serta terukur. Setyawati, Aryani and Ningrum (2018) berpendapat bahwa kinerja karyawan adalah hasil yang dicapai oleh seseorang karyawan dalam melaksanakan tugasnya sesuai dengan tanggungjawab yang diberikan kepadanya. Menurut Riyadi, (2011) penentu kinerja karyawan dapat dibagi kedalam dua faktor utama, yaitu faktor internal dan faktor eksternal.…”
Section: Tinjauan Pustaka Kinerja Karyawanunclassified
“…Hasil analisis regresi melalui uji hipotesis, penelitian ini mendukung hipotesis 1, bahwa lingkungan kerja berpengaruh positif dan signifikan terhadap kinerja karyawan Pinatih and Gorda, 2017;Lukito and Alriani, 2018;Setyawati, Aryani and Ningrum, 2018) menunjukkan sebaliknya, bahwa stres kerja berpengaruh negatif terhadap kinerja karyawan. Menurut Handoko (2001) sejalan dengan meningkatnya stres dapat membantu karyawan untuk mengarahkan segala sumber daya yang dimilikinya dalam memenuhi berbagai persyaratan atau kebutuhan pekerjaan.…”
Section: Pembahasan Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawanunclassified
See 1 more Smart Citation